Commercial forestland investments - Olsson, Mikael; Sparrevik, Gustaf (2021)
Since the early 1990s interest rates have been decreasing, which has led to lowered yield on traditional secure financial assets as bonds. It has resulted in a flow of capital in the financial market towards alternative investments in the search for yield beyond the stock market. The forest asset has traditionally been desirable in a portfolio for the diversification aspect associated with the unique characteristic of the biological growth being uncorrelated to the financial markets. However, the interest in forestland investments has become more diverse through the monetization of non-timber values. In Sweden, the price of forestland available for purchase by juridical persons has increased rapidly since the abolishment of the price regulation in the early 1990s. This study aims to identify forest owner categories of commercial forest investors within the Swedish forestland property market.